APPLICATION OF DRAW WIRE SENSOR IN POSITION TRACKING OF ELECTRO HYDRAULIC ACTUATOR SYSTEM - Rahmat, Mohd Fua'ad; Md. Rozali, Sahazati; Abdul Wahab, Norhaliza; Has, Zulfatman (2010)
Draw-wire sensor is classified as a contact measurement method. This sensor is ideal for applications with large measuring ranges, small sensor dimensions and when a low cost solution is required. The objective of this research is to explain the application of a draw-wire sensor in position tracking of electro-hydraulic actuator system. The work started with the modeling of the electro hydraulic actuator system. Draw wire sensor is attached to the load of electro hydraulic system to measure its motion when an input signal is injected to the system. The sensor output is the displacement in millimeter and converted to the voltage based on the input signal given. These input and output readings are collected and applied to a system identification procedure in order to obtain the best mathematical model of the system. The modeling process is followed by designed a proportional integral and derivative controller (PID) for the system to assure the output is tracking the input given. The designed controller is applied to the system in both simulation and real time mode. The output performance of the system for these two modes is compared and it can be seen that the simulation and real-time output are almost similar. The overall process of this work shows the important role of draw wire sensor in capturing the output data of the electro hydraulic actuator system precisely either with or without controller. Other displacement transducer might be used in future work of position tracking of electro-hydraulic actuator system.